2010
DOI: 10.4055/cios.2010.2.2.112
|View full text |Cite
|
Sign up to set email alerts
|

Revision Total Knee Arthroplasty with a Cemented Posterior Stabilized, Condylar Constrained or Fully Constrained Prosthesis: A Minimum 2-year Follow-up Analysis

Abstract: BackgroundThe clinical and radiological outcomes of revision total knee arthroplasty with a cemented posterior stabilized (PS), condylar constrained knee (CCK) or a fully constrained rotating hinge knee (RHK) prosthesis were evaluated.MethodsThis study reviewed the clinical and radiological results of 36 revision total knee arthroplasties with a cemented PS, CCK, and RHK prosthesis in 8, 25, and 13 cases, respectively, performed between 1998 and 2006. The mean follow-up period was 30 months (range, 24 to 100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 22 publications
0
52
0
2
Order By: Relevance
“…The poorer results of revisions have been attributed to several factors including the deficiency of host bone stock both in quantity and quality, extensor mechanism problems, ligamentous instability [5] and a greater incidence of periprosthetic infection [6]. Numerous studies have reported rates of reoperation after revision TKA of eight to 19 % [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The poorer results of revisions have been attributed to several factors including the deficiency of host bone stock both in quantity and quality, extensor mechanism problems, ligamentous instability [5] and a greater incidence of periprosthetic infection [6]. Numerous studies have reported rates of reoperation after revision TKA of eight to 19 % [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of factors that complicate surgery, such as bone defects and ligament imbalances were high in many of the patients undergoing revision surgery and we believe that these factors contributed to the secondary revision rate which was at the higher limit of the range reported in the literature (11,14). The objective outcomes and patient satisfaction for revision TKA are lower when compared to primary TKA (16).Ching-Jen Wang et al conducted a study comparing clinical and functional outcomes and patient satisfaction between patients who underwent revision for aseptic or septic reasons (17).In this study, they reported that patient satisfaction and joint range of motion were higher after aseptic revisions, while there was no significant difference in terms of pain and functional scores. In the present study, the mean clinical knee score was 86.5 and the mean functional knee score was 68.6 in patients who underwent aseptic revision.…”
Section: Discussionmentioning
confidence: 99%
“…The designs and types of prostheses used in revision surgery vary widely depending on the individual difficulties in each patient (17). Prosthesis selection varies depending on the patient, the technique preferred by the surgeon and available prosthesis options.…”
Section: Discussionmentioning
confidence: 99%
“…32 In general, a cemented PS prosthesis was used if both collateral ligaments were felt to be competent, and a CCK or RHK prosthesis was used if both collateral ligaments were incompetent. RHK was considered in case of extensor mechanism failure, soft tissue incompetence, severe bony defects, and flexion gap imbalance.…”
Section: Discussionmentioning
confidence: 99%